Luchamos por nuestros hijos: Latino immigrant parents strive to protect their children from the deleterious effects of anti-immigration policies. (April 2016) - Philbin, Sandy P.; Ayón, Cecilia
Abstract: The purpose of this study is to examine the strategies used by Latino immigrant parents to protect their children from the deleterious effects of anti-immigration policies. In-depthsemi-structured interviews were conducted with 54 immigrant parents. Informed by constructivist grounded theory, a constant comparative approach was used between and within transcripts during initial and focused coding. Our study highlights the strength and resiliency of immigrant parents as they strive to mitigate the harm of anti-immigrant policies on their children. Common strategies to protect their children focus on securing and promoting safety and well-being( let children live their childhood, be prepared, consejos ), enhancing their own capacity to provide ( pursue education, obtain papers ), and engaging in change efforts within their community. Parents believed these efforts could diminish the negative effects of anti-immigration policies. Immigrant Latino communities will be better served in the future if engaged professionals incorporate empowerment and strength based models within their practice. Highlights: Latino parents are resilient and actively engage in efforts to protect their children from the harmful effects of anti-immigrant policies. Strategies used by parents involved the parent-child relationship, building their capacity, and changing their local environment. Social work practice with Latino immigrant families need to be informed by empowerment and strength based models.